The framing of innovation among European research funding actors: Assessing the potential for 'responsible research and innovation' in the food and health domain. (July 2016) - Khan, Shumaisa S.; Timotijevic, Lada; Newton, Rachel; Coutinho, Daniela; Llerena, José Luis; Ortega, Santiago; Benighaus, Ludger; Hofmaier, Christian; Xhaferri, Zamira; de Boer, Alie; Urban, Christine; Strähle, Michael; et al.
Highlights: Examines framing of innovation among research funding decision makers. Innovation perceived to be focused on biosciences and marketable applications. Inadequate consideration of normative issue of who defines the problems. Shift in framing is necessary to implement responsible research and innovation. Abstract: Responsible Research and Innovation (RRI) has recently emerged as a new framework for science and technology governance. The concept articulates the need for mutual exchange by which societal actors become responsive to each other early on in the process of innovation, with a view to facilitate ethically acceptable and sustainable innovation. There is relatively limited evidence to explore the extent to which the process of research and innovation under the terms of RRI is realised in practice, particularly in the context of food and health research. Although research to date has been examining innovation from the point of view of inputs and outputs—R&D funding and patents—we propose to examine the cognitive framing of innovation that shapes decisions of those who constitute a part of the innovation chain. This paper explores how the concept of innovation is understood and used in policy implementation, with a particular focus upon 'food and health' science and research policy and funding. Our analysis is based on 55 interviews of various actors engaged in research funding decision-making across eight European countries. Three themes emerged from the analysis: concept of innovation; conditions for innovation; and drivers of innovation; through these themes, the cognitive framing was drawn out. The cognitive framing suggests that innovation in the food and health domain is perceived to be focused on biosciences and marketable applications to the neglect of social sciences and broader public interest; that the "innovation network" is primarily viewed as centred around scientific/technical and industrial actors; and that the demand-pull dynamic is relevant to innovation in the area of food and health, despite having been relegated in contemporary thinking and policies around innovation. These findings point to the inadequate consideration of the normative issues—how problems are to be defined and addressed—among national research funders in the food and health domain, and indicate a gap between the ideas of innovation under the terms of RRI and innovation as conceptualised by those involved in its governance.